Quantum consistency of the superstring - Berkovits, Nathan [UNESP] (Springer Nature, 2005)
Using arguments based on BRST cohomology, the pure spinor formalism for the superstring in an AdS 5×S 5 background is proven to be BRST invariant and conformally invariant at the quantum level to all orders in perturbation theory. Cohomology arguments are also used to prove the existence of an infinite set of non-local BRST-invariant charges at the quantum level. © SISSA 2005.
Keywords: AdS-CFT and dS-CFT Correspondence; Superstrings and Heterotic Strings